Plate Theory and Extensions - The Plate Theory > Page 8

                                            

Integrating,                        logeXo(m)  =   -v + K

Now,                              when v = 0,       logeXo(m) =

Consequently,    Thus,     logeXo(m)  = -v + logeXo

 

or                                       X(m)o   =  Xoe-v                           (10)       

                                                      (11)

                                                                     

Substituting for Xm(0) from (10) in (11),